Two progressive pathways of microinvasive carcinoma: low-grade luminal pathway and high-grade HER2 pathway based on high tumour-infiltrating lymphocytes. Issue 10 (30th March 2016) - Morita, Michi; Yamaguchi, Rin; Tanaka, Maki; Tse, Gary M; Yamaguchi, Miki; Otsuka, Hiroko; Kanomata, Naoki; Minami, Shigeki; Eguchi, Susumu; Yano, Hirohisa
Abstract : Aims: While cancer immunity is involved in tumour progression from the very early stage, no detailed study has been reported on the relationship between 'early-stage' breast cancer and tumour-infiltrating lymphocytes (TILs). We focused on microinvasive carcinoma to investigate the relationship between histological tumour factors and immunity in 'early' breast cancer. Methods: Of 2593 resected breast carcinomas, 46 microinvasive carcinomas (1.8%) were included. The relationships between tumour characteristics (invasive form, grade, comedo, subtype) and immunological characteristics (TIL, healing) were examined. The invasive form was divided into 'cluster-like' (ie, invasive foci consisted of a small number of cancer cells) and 'non-cluster-like' (ie, nested and classifiable into particular histological type). Results: Among all cases, 34.8% were grade 1. ER+HER2−, ER+HER2+, ER−HER2+ and ER−HER2− accounted for 58.7%, 8.7%, 28.3% and 4.3%, respectively. Compared with ER+HER2−, ER−HER2+ cases had a significantly stronger association with grade 3 (92.3% vs 0%), comedo (100% vs 55.6%), high TIL (100% vs 29.3%), high CD8+ TIL (92.3% vs 33.3%) and healing (76.9% vs 14.8%) (p<0.001). Compared with 'non-cluster-like', 'cluster-like' carcinoma showed significantly higher rates of HER2 positivity (69.2% vs 24.2%), high TIL (92.3% vs 42.4%) and high CD8+ TIL (76.9% vs 39.4%) (p<0.01). Conclusions: Our study revealed that microinvasive carcinoma has two progressive pathways; 'low-grade luminal pathway' and 'high-grade HER2 pathway'. HER2-positive cases showed the following unique characteristics: 'high-grade; comedo, high TIL and CD8+ TIL; healing; cluster-like invasion'. These results suggest that the cluster-like invasion might occur because of tumour immunity that leads to disruption of the duct and formation of microinvasive carcinoma in HER2-positive cases.